Teaching Culture of Others through English Literature : English - Latifatul Isro’iyah; Dwi Ima Herminingsih (International Journal of Language and Literary Studies, 2023)
The diversity of the culture in the world is a given thing. Billions of people from different countries in the world have produced varieties of civilizations, ways of life, lifestyle, custom, heritage, habits, values, and traditions. It is hypothesized understanding the culture of different people can be valuable to the student’s character building. The comprehension of multicultural can be modality to be more aware of cultural dissimilarities. They can respect any variance of people whose backgrounds, minds, opinion and may behave in ways that are not the same. Besides, the possession of rich knowledge of diverse cultures can bridge them to take interpersonal communication in friendly ways. Nonfiction kinds of literature, science books as well as historical books are not the only sources to study multicultural. Doing literature reading comprehension is another method to open the horizon of the existing variability of culture. The paper presents descriptively the teaching experience of how the students of the University in Tulungagung, Indonesia got to practice learning the culture of people in different areas of the world through extensive reading. The teaching materials cope with the introduction of the theory of literature, how are the cultures told by the author, and why is it important to comprehend literature? How multicultural literacy has inspired the students ’live performance. The teaching goal aims to let the students learn something good or positive about the culture of people of others delivered by the writers of poems, novels, and drama. The broader insights of life experiences, religion, beliefs, and customs of other people can bridge the friendship of ethnicity, race, and social status across the world. Being not a closed mind human beings can appreciate or respect others, avoid underestimating, bullying, any violence, and being the right, the best, and the richest person.